2006
DOI: 10.1191/0961203306lu2340oa
|View full text |Cite
|
Sign up to set email alerts
|

Hand Arthritis in Systemic Lupus Erythematosus: An Ultrasound Pictorial Essay

Abstract: A small minority of systemic lupus erythematosus (SLE) patients may develop a deforming arthritis, typically with a non-erosive (Jaccoud's) pattern, although erosive features indistinguishable from rheumatoid arthritis may also occur. High-resolution ultrasonography (HRUS) allows detailed 'real time' imaging of joint and tendon morphostructural changes involving the hand in patients with several rheumatic diseases. The main aim of this pictorial essay is to provide the first descriptive HRUS and power Doppler … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(65 citation statements)
references
References 16 publications
2
61
2
Order By: Relevance
“…Secondly, joint deformities are observed in up to 35% of patients and appear to be associated with difficulties in performing daily activities and may require surgery [10]. Finally, ultrasound studies have shown an unexpected high prevalence of synovitis, tenosynovitis and erosions also in SLE patients (Table 4) [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Secondly, joint deformities are observed in up to 35% of patients and appear to be associated with difficulties in performing daily activities and may require surgery [10]. Finally, ultrasound studies have shown an unexpected high prevalence of synovitis, tenosynovitis and erosions also in SLE patients (Table 4) [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory alterations have been detected by US in the hand or wrist in up to 80% of unselected SLE patients and in more than 90% of patients with joint involvement [12][13][14][15][16]. Moreover, in the few small studies on SLE, MRI demonstrated good performances in the identification of structural damage and bone marrow edema (BME) which have been described in up to 94% and 14%, respectively, of patients with joint involvement [17][18][19].…”
Section: Introductionmentioning
confidence: 98%
“…[7][8][9] The details of some of these studies have been reviewed elsewhere, 10 but all studies noted a higher than expected prevalence of synovitis, tenosynovitis and erosions than was estimated from clinical examination. The presence of erosions can obscure the boundary between SLE and rheumatoid disease.…”
Section: Introductionmentioning
confidence: 99%
“…connective tissue diseases or vasculitis) it has not been used or has been poorly applied. The role of US in SLE has been reported by two studies which show the high frequency of subclinical joint involvement [54,55]. Also preliminary studies on the evaluation of knee and hands in Sjögren syndrome gave promising results [56,57].…”
Section: The Omeract Special Interest Group On Us Ismentioning
confidence: 96%